The 2nd International Conference of Ia ValSe-Food Network 2020
DOI: 10.3390/proceedings2020053004
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Nutritional Composition of Quinoa According to the Processing Used

Abstract: Quinoa is consumed as a seed, flour, expanded, sprout (germinated) and activated (hydrated). The objective of this work was to determine the nutritional composition of the different preparations. The same batch of quinoa seeds was processed as flour, expanded, hydrated and germinated. It showed that there is a statistically significant difference of nutrients between all groups. For proteins, it varies from 12.78 ± 0.02 g/100 g in whole seed to 5.25 ± 0.01 g/100 g in the hydrated seed. In total fats, it varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…These values are comparable with the values obtained for the leaves of amaranth and spinach [12] and C. album [13,42]. Only two studies reported that quinoa sprouts are also rich in K and Mg, and the values are 525.0 and 219.0 mg 100 g −1 , respectively [29,39].…”
Section: Mineralssupporting
confidence: 88%
See 1 more Smart Citation
“…These values are comparable with the values obtained for the leaves of amaranth and spinach [12] and C. album [13,42]. Only two studies reported that quinoa sprouts are also rich in K and Mg, and the values are 525.0 and 219.0 mg 100 g −1 , respectively [29,39].…”
Section: Mineralssupporting
confidence: 88%
“…Alternatively, Chacaliaza-Rodríguez et al (2016) [22] used fresh leaf quinoa and reported that protein was low, about 4.6% at 86.4% moisture content. Quinoa sprouts contain a low amount of protein ranging from 6.1 to 12.3% [30,39]. Protein content in C. album dry and fresh leaf was about 28.7 and 5.0%, respectively [13,44].…”
Section: Proteinmentioning
confidence: 99%
“…The minimum value in our samples is below those found by [21,34,35], which reported minimum values of 5.5%, 5%, and 4.54%, respectively. Another study that analyzed samples from the same lot located in Argentina found a value of 2.3% fat [40]. In a review about chemical composition of quinoa with studies prior to the year 2000 [41], it was reported that the fat content in quinoa seeds ranges between 1.8% and 9.5%.…”
Section: Water Activity and Proximate Compositionmentioning
confidence: 99%
“…In general, the fat content was lower in sprouted quinoa (0.1-3.8%) [65,66] than in its grain (4.0-7.6%) [67]. The fat content of sprouted grains generally decreases because of the use of lipids as an energy source during germination [68] or increased lipolytic activity, which converts fats into fatty acids and glycerol [69][70][71].…”
Section: Lipid Content Of Sprouted Grainsmentioning
confidence: 99%